Keys to Successful Civil Servant Performance in the Digital Era: Explaining the Role of Visionary-Participative Leadership and Digital Technology Literacy - Yunita Tri Susilowati; Emiliana Sri Pudjiarti; Agustin Nurcahyanti; Hendrik Setiawan; Yulia Adityorini (Journal of Management and Social Sciences, 2024)
This study investigates the correlation between visionary-participative leadership style, digital technology literacy, employee involvement, and civil servant performance within the digital transformation context of the Semarang City Regional Revenue Agency. Employing a quantitative methodology, a survey of 105 staff members is conducted. The investigation in this research utilized Structural Equation Modeling methodologies employing the Partial Least Squares (PLS-SEM) framework. This study underscores the significance of adopting a holistic method toward advancing human capital by combining the improvement of digital competencies with tactics to enhance employee involvement. Study findings indicate that digital technology literacy skills substantially and constructively influence employee engagement and performance. Visionary-participative leadership positively impacts employee engagement, yet its direct effect on performance is deemed insignificant. Employee involvement is demonstrated to have a significant and favorable impact on performance. Theoretical and practical implications emphasize the necessity of crafting a more tailored digital transformation framework for the public sector and the importance of revamping leadership development initiatives to address the intricacies of bureaucracy in the digital age.